Study of the Environmental Factors Affecting the Abundance of the Asian Catfish H.1843 Silurus triostegus in the Hammar Marsh - kamel; Sarah (University of Thi-Qar Journal of agricultural research, 2025)
Fish are among the most important organisms in aquatic ecosystems due to their nutritional, economic, and environmental value. This study focused on the impact of environmental factors—including temperature, salinity, pH, and dissolved oxygen—on the feeding behavior of the Asian catfish (Silurus triostegus) in the Al-Hammar Marsh, Dhi Qar Province, southern Iraq.A total of 60 fish samples were collected over a six-month period (October 2024 to March 2025), with 10 samples per month. Stomach contents were analyzed using the point method. The results showed the highest feeding activity occurred in October and November, where most stomachs were full or half-full (scores of 20 or 10). In contrast, December and January recorded the highest percentage of empty stomachs (score 0), reflecting reduced feeding activity likely due to environmental fluctuations.Biochemical analyses revealed a decrease in protein and fat content in muscle tissues from the beginning to the end of the study: protein decreased from 19% to 16.7%, and fat from 0.13% to 0.07%. Moisture content increased from 76.4% to 80.04%, and ash content from 1.01% to 1.24%. Similar patterns were observed in liver tissues, where protein dropped from 17.6% to 14.18%, and moisture increased from 71.86% to 73.7%.These findings demonstrate that environmental factors directly influence the feeding patterns and nutritional condition of Asian catfish. The study highlights the importance of monitoring aquatic environmental conditions to support fish health, growth, and sustainable fishery management.